Common variants in the GDF5-UQCC region are associated with variation in human height - Sanna, Serena; Jackson, Anne U; Nagaraja, Ramaiah; Willer, Cristen J; Chen, Wei-Min; Bonnycastle, Lori L; Shen, Haiqing; Timpson, Nicholas; Lettre, Guillaume; Usala, Gianluca; Chines, Peter S; Stringham, Heather M; et al. (Nature genetics, 2008)
Identifying genetic variants that influence human height will advance our understanding of skeletal growth and development. Several rare genetic variants have been convincingly and reproducibly associated with height in mendelian syndromes, and common variants in the transcription factor gene HMGA2 are associated with variation in height in the general population 1 . Here we report genome-wide association analyses, using genotyped and imputed markers, of 6,669 individuals from Finland and Sardinia, and follow-up analyses in an additional 28,801 individuals. We show that common variants in the osteoarthritis-associated locus 2 GDF5-UQCC contribute to variation in height with an estimated additive effect of 0.44 cm (overall P < 10 −15 ). Our results indicate that there may be a link between the genetic basis of height and osteoarthritis, potentially mediated through alterations in bone growth and development.